PENGARUH SELF REGULATION LANGUAGE PADA KEMAMPUAN MENYIMAK SISWA KELAS IV SDN 207/IV - oktarizka, dhea annisa (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
The basis that must be mastered in Indonesian language learning content is linguistic mastery which consists of listening, speaking, reading, and writing skills. Students' ability to listen is included in the basic skills in learning activities at school, especially in Indonesian language content. This study aims to determine the effect of self-regulation language on students' listening skills in elementary schools. This study uses a quantitative approach using the partial least square structural equation modeling (PLS-SEM) technique. The population in this study was 100 students of grade IV SD as well as the sample for this study 100 students of grade IV SD. The result of this research is the effect of self-regulation on the listening ability of fourth grade elementary school students